The Influence of Product Diversification, Service Quality, and Risk Management of Islamic Banks on Money Market Stability in Indonesia - Pratama, Wilson Candra Teguh; Judijanto, Loso; Jasmin, Jasmin; Purnamasari, Eva (Westscience Press, 2024)
This study investigates the effect of Product Diversification, Risk Management, and Service Quality of Islamic banks on Money Market Stability in Indonesia. Using quantitative analysis based on Structural Equation Modeling with Partial Least Squares (SEM-PLS), data were collected through a survey of Islamic bank customers. The results reveal significant positive relationships between Product Diversification, Risk Management, Service Quality, and Money Market Stability. Product Diversification positively influences Service Quality and Risk Management, while Service Quality and Risk Management, in turn, positively impact Money Market Stability. The findings underscore the importance of adopting comprehensive strategies to enhance the stability of the money market in Indonesia's Islamic banking sector. These insights have implications for practitioners, policymakers, and researchers aiming to promote financial stability and inclusivity in Islamic finance.